'Am I the only one here who sees the alien': Science in Invader ZIM. Issue 2 (1st June 2013) - Gil, Steven
Science Fiction (SF) articulates many of the central issues faced in culture and society and none greater than the role, capacities and implications of scientific knowledge. As a genre it displays a heightened capacity to engage in philosophical debates giving salient insights. Contemporary scientific knowledge or 'mainstream science' provides the critical grounding on which the extraordinary worlds of SF are naturalized. However, complete adherence to known facts would render SF incapable of facilitating the speculative dimensions in which it revels. To counter-balance this, marginal science is often engaged as a means to extend the known and explore new possibilities whilst maintaining a noticeable link to scientific rationality. Invader ZIM (Nicktoon Productions 2001-2003, 2006), an animated television (TV) series about an alien's efforts to conquer Earth and the attempts of a young paranormal enthusiast to stop him, provides a way to articulate this positioning of science.